The effect of entrepreneurial leadership on employee’s creativity and sustainable innovation performance in education sector: a literature review - Ibrahim, Abdulhadi; Al-Refaei, Abd Al-Aziz; Alshuhumi, Said; Abdulmalek Yahya Al-Hidabi, Dawood; Ateeq, Ali (Springer, 2024)
Abstract In today’s business landscape, possessing solely leadership or entrepreneurship qualities is insufficient for the success of enterprises. Successful managers must possess a combination of leadership and entrepreneurship attributes that can affect their employee’s creativity and sustainable innovation performance. In a constantly evolving and unpredictable business environment, the importance of entrepreneurial leadership in influencing sustainable organizational performance cannot be emphasized enough. In this literature review, we have examined the complex aspects of entrepreneurial leadership and its significant impact on employees’ creativity and sustainable innovation organizational performance in education sectors and contexts. the results revealed that Entrepreneurial leadership was found to have a direct impact on employees’ creativity and sustainable innovation performance, and employees’ creativity could mediate the relationship between entrepreneurial leadership and sustainable innovation organizational performance. Entrepreneurial leadership is not merely a leadership style, but rather a powerful force that can redefine the operations, innovation, and success of organizations. The study provides direction for future research.